1985
DOI: 10.1002/ana.410170607
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative contrast enhancement in patients with brain tumor

Abstract: Contrast enhancement resulting from surgical trauma may mimic residual enhancing tumor, thereby complicating the interpretation of postoperative computed tomographic scans. We assessed the natural history of postoperative enhancement in 10 patients with brain tumor. Contrast enhancement distinguishable from residual enhancing tumor appeared along the operative margin following tumor resections but not lobectomies. Enhancement appeared as early as the fifth postoperative day, was most intense at two weeks, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(37 citation statements)
references
References 10 publications
0
36
0
1
Order By: Relevance
“…Further complicating any attempt to analyze the impact of residual tumor observed on radiographs was the interval between surgery and postoperative imaging; the average time from resection to CT scanning was 6 days in our study. Authors of both animal [24] and clinical reports [6,7,9] have recommended performing CT scans within 2 to 4 days of surgery, to avoid spurious enhancement from the development of reactive neovascularity and breakdown of the blood-brain barrier in the tumor bed. Even with early scans, enhancement may occur in biopsy-negative resection margins of pediatric brain tumors only to disappear on subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further complicating any attempt to analyze the impact of residual tumor observed on radiographs was the interval between surgery and postoperative imaging; the average time from resection to CT scanning was 6 days in our study. Authors of both animal [24] and clinical reports [6,7,9] have recommended performing CT scans within 2 to 4 days of surgery, to avoid spurious enhancement from the development of reactive neovascularity and breakdown of the blood-brain barrier in the tumor bed. Even with early scans, enhancement may occur in biopsy-negative resection margins of pediatric brain tumors only to disappear on subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of alterations in tumour extent with therapy using computerized tomography (CT) and magnetic resonance imaging (MRI) can be a problem for gliomas where the tumour can not be clearly delineated from post-operative enhancement (Cairncross et al, 1985) and radiation-induced necrosis and prognosis (Alavi et al, 1988 (Valk et al, 1988). It has been proposed that changes in […”
mentioning
confidence: 99%
“…Enhancement of the dura mater was not seen before 2 weeks and was limited to the area beneath the craniotomy. In this and other studies, the enhance ment was interpreted as due to reactive vascular changes and neovascularity, based on the microscopic pathology and time delay in onset [5,8,9]. This led to the recom mendation for clinical postoperative scanning within 7 days of surgery to best define residual tumor [5,8], Cairncross et al [5] reported a series of patients undergoing serial scans after craniotomy for tumor resec tion.…”
Section: Discussionmentioning
confidence: 99%
“…Some treatment protocols mandate different treatment for patients with residual disease. Patients with residual disease may be subjected to more aggressive or more promptly instituted adjunctive therapies [5,6]. In fact, a measurable disparity between the incidence of true residual neoplasm and con trast enhancement on CT scans obtained within 3 days of craniotomy has been demonstrated [7], It had been sug gested that scanning patients even earlier than 72 h would further reduce the incidence of these artifacts [7].…”
Section: Introductionmentioning
confidence: 99%